2019
DOI: 10.1002/pbc.27820
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of entinostat alone and in combination with standard‐of‐care cytotoxic agents against rhabdomyosarcoma xenograft models

Abstract: Background: Entinostat, a selective class I histone deacetylase inhibitor, has been reported to enhance the activity of cytotoxic agents and suppress expression of PAX3-FOXO1 in alveolar rhabdomyosarcoma (ARMS). Procedures: Entinostat was tested against three rhabdomyosarcoma cell lines using 96-hour drug exposure. Entinostat alone or in binary combination with vincristine, actinomycin D or cyclophosphamide was tested in ARMS and two embryonal rhabdomyosarcoma (ERMS) xenograft models. Tumor growth was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
(67 reference statements)
0
19
0
Order By: Relevance
“…This also applies to the doses that can be achieved without significant toxicity in RCC patients. A recent report found that up to 1.51 µM MS-275 was achieved without gross toxicity in mice, but large variation of maximal plasma concentrations from 4 to 53.1 ± 92.4 and a half-life from 33.4 to 150 h occurred in humans (Connolly et al 2017;Kurmasheva et al 2019), indicating unexplained large patient-to-patient variability. The maximum-tolerated dose of VPA was reported to range, for example, from 50 mg/kg daily to 140 mg/kg/day, which is within the therapeutic serum concentrations of VPA from 0.35 to 0.7 mM (Bug et al 2005;Münster et al 2007;Phiel et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This also applies to the doses that can be achieved without significant toxicity in RCC patients. A recent report found that up to 1.51 µM MS-275 was achieved without gross toxicity in mice, but large variation of maximal plasma concentrations from 4 to 53.1 ± 92.4 and a half-life from 33.4 to 150 h occurred in humans (Connolly et al 2017;Kurmasheva et al 2019), indicating unexplained large patient-to-patient variability. The maximum-tolerated dose of VPA was reported to range, for example, from 50 mg/kg daily to 140 mg/kg/day, which is within the therapeutic serum concentrations of VPA from 0.35 to 0.7 mM (Bug et al 2005;Münster et al 2007;Phiel et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, entinostat was also evaluated in combination with chemotherapy in mouse models for rhabdomyosarcoma and was not found to enhance the standard therapy 17 . Preclinical studies with entinostat have found a synergistic effect with check point inhibitors and in combination with hormonal therapy for patients with homone receptor‐positive, HER2‐negative breast cancers, but clinical trials have yet to demonstrate a clinical benefit 18–21 . As more preclinical data in immunomodulation in pediatric solid tumors becomes available the role of entinostat in immunomodulation and if a synergistic effect will need to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…We next evaluated whether this sequential drug treatment strategy would work in vivo. H1299 cells were implanted into non-obese diabetic scid gamma (NSG) mice and treated with sequential injections of DAC and ENT both at a dose of 2.5 mg/kg according to published protocols ( Figure 5D) (35)(36)(37). As shown in Figure 5D-E, tumors were monitored and measured on day 17, 24, and day 31, and were harvested on day 32 after various treatments.…”
Section: Dac Pre-treatment Can Prime Sall4 Negative Cells To Be Targementioning
confidence: 99%